Nitrile rubber composition, crosslinked nitrile rubber member, and sealing member
A nitrile rubber composition with artificial graphite addresses the challenge of reducing torque in oil seals by creating a crosslinked member with low friction and maintained tensile strength, ensuring effective sealing and conductivity.
Patent Information
- Application Number
- JP2021036133
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-08
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2041-03-08
AI Technical Summary
Existing methods to reduce the torque of oil seals, such as adjusting seal shape and grease composition, compromise the sealing performance of oil seals.
A nitrile rubber composition containing artificial graphite, with specific particle size and content, is used to create a crosslinked nitrile rubber member with low friction and maintained tensile strength, suitable for use in oil seals.
The crosslinked nitrile rubber member provides a sealing member with low torque performance and electrical conductivity while maintaining sealing effectiveness.
Smart Images

Figure 0007627581000001 
Figure 0007627581000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a nitrile rubber composition, a crosslinked nitrile rubber member, and a sealing member. [Background technology]
[0002] In recent years, with the demand for energy saving, there is a demand for lower torque oil seals. One type of oil seal for which lower torque is desired is an oil seal used in the hub unit of an automobile (also referred to as a hub seal in this specification).
[0003] Various methods have been considered as techniques for reducing the torque of oil seals. For example, methods are being considered for changing the shape of the seal to a shape suitable for reducing torque, and methods are also being considered for changing the composition of the grease to a blend suitable for reducing torque (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-088527 A Summary of the Invention [Problem to be solved by the invention]
[0005] On the other hand, when attempts are made to reduce the torque of an oil seal by techniques such as making the seal shape suitable for low torque or by adjusting the grease composition to suit low torque, the sealing performance of the oil seal may be reduced.
[0006] The present inventors have conducted extensive research to solve these problems, and have found a nitrile rubber composition suitable for providing a seal member that is excellent in low torque while maintaining sealing performance, thereby completing the present invention. [Means for solving the problem]
[0007] (1) The nitrile rubber composition of the present invention contains nitrile rubber and artificial graphite, The content of the artificial graphite is 30 to 100 parts by mass relative to 100 parts by mass of the nitrile rubber. According to the above nitrile rubber composition, it is possible to provide a crosslinked nitrile rubber member having a low friction coefficient without significantly impairing the tensile strength at break. By using this crosslinked nitrile rubber member, it is possible to provide a seal member suitable for reducing torque.
[0008] (2) In the nitrile rubber composition, the average particle size of the artificial graphite is preferably 1 to 10 μm. In this case, the crosslinked nitrile rubber member, which is a crosslinked product of the nitrile rubber composition, has a low volume resistivity and exhibits good electrical conductivity. Therefore, by using the nitrile rubber composition, it is possible to provide a sealing member that requires low torque performance and electrical conductivity.
[0009] (3) The crosslinked nitrile rubber member of the present invention comprises a crosslinked product of the nitrile rubber composition described in (1) or (2) above. The crosslinked nitrile rubber member has a low coefficient of friction and is suitable as a rubber member for use in the lip portion of a seal member.
[0010] (4) The sealing member of the present invention has a lip portion made of the crosslinked nitrile rubber member described in (3) above. The seal member includes a lip portion made of the crosslinked nitrile rubber member, and therefore is a seal member that maintains sealing performance and has excellent low torque performance. Effect of the Invention
[0011] According to the present invention, it is possible to provide a seal member excellent in low torque performance, and to provide a nitrile rubber composition and a crosslinked nitrile rubber member suitable for providing this seal member. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described. [Nitrile rubber composition] The nitrile rubber composition according to an embodiment of the present invention contains uncrosslinked nitrile rubber and artificial graphite.
[0013] The above-mentioned nitrile rubber (NBR) is also called acrylonitrile-butadiene rubber and is a copolymer whose monomer components are acrylonitrile and butadiene. In the present invention, the nitrile rubber may be a copolymer containing, in addition to acrylonitrile and butadiene, monomers other than these as monomer components. The nitrile rubber may also be hydrogenated nitrile rubber (HNBR) in which the remaining double bonds in the main chain are hydrogenated.
[0014] The amount of bound acrylonitrile (hereinafter also referred to as AN amount) of the nitrile rubber is not particularly limited. The nitrile rubber may be a wide variety of types, from those with a low nitrile amount of 24% by mass or less to those with a high nitrile amount of more than 35% by mass. When the nitrile rubber composition is intended to provide a hub seal as a sealing member, for example, the nitrile rubber is preferably a medium nitrile type having an AN amount of 25 to 30 mass %, because it is suitable for ensuring a good balance of the characteristics required for the hub seal.
[0015] The nitrile rubber preferably has a Mooney viscosity "ML(1+4)100°C" of 35 to 65. The Mooney viscosity may be measured in accordance with JIS K6300-1 (2013). In this case, it is easy to form a crosslinked product having normal physical properties suitable for a sealing member. As the nitrile rubber, commercially available products can also be used.
[0016] The above nitrile rubber may be used alone or in combination with two or more different types having different AN amounts, Mooney viscosities, the presence or absence of hydrogenation, types of monomer components, etc.
[0017] The artificial graphite is produced, for example, by calcining coke made from petroleum, coal or the like, and then graphitizing it at high temperatures. It is important that the nitrile rubber composition contains artificial graphite as graphite particles. By using a nitrile rubber composition containing a predetermined amount of artificial graphite as a raw material for a seal member, it is possible to obtain a seal member that ensures desired normal state properties and can achieve low torque. For example, when natural graphite is used as the graphite to be blended in the nitrile rubber composition, the natural graphite has a lower hardness than artificial graphite, and therefore the effect of contributing to lower torque of the sealing member is poor. In addition, when natural graphite is used, the tensile strength at break (Tb) and elongation at break (Eb) become small because the shape of natural graphite is mainly scaly, thin, or other shapes other than spherical.
[0018] The shape of the artificial graphite is preferably spherical or close to spherical. On the other hand, it is preferable to avoid flaky or thin graphite, which is often seen in natural graphite. When graphite is contained in the nitrile rubber composition, the crosslinked product tends to have a lower tensile strength at break. In this case, when spherical artificial graphite is contained, the degree of decrease in tensile strength at break can be reduced. Therefore, the crosslinked product of the nitrile rubber composition containing spherical artificial graphite achieves a low friction coefficient (low μ) while suppressing the decrease in tensile strength at break caused by the inclusion of artificial graphite.
[0019] The average particle size of the artificial graphite is preferably 1 to 10 μm. Artificial graphite having an average particle size of less than 1 μm is practically difficult to obtain, and even if it is available, it is very expensive. On the other hand, if the average particle size of the artificial graphite exceeds 10 μm, the obtained cross-linked product and a sealing member using this cross-linked product have a high volume resistivity and poor electrical conductivity. A more preferred lower limit of the average particle size of the artificial graphite is 2 μm, and a further more preferred lower limit is 4 μm, while a more preferred upper limit of the average particle size of the artificial graphite is 8 μm.
[0020] The average particle size of the above artificial graphite is the median size (D50) in a volume-based particle size distribution measured using a laser diffraction / scattering method. The artificial graphite may be in the form of primary particles or secondary particles.
[0021] As the artificial graphite, commercially available products can also be used. An example of the commercially available product is PAG-1500 (manufactured by Nippon Graphite Industries Co., Ltd.).
[0022] The content of the artificial graphite is 30 to 100 parts by mass relative to 100 parts by mass of the nitrile rubber. In this case, it is possible to provide a crosslinked product of the nitrile rubber composition having a low friction coefficient and physical properties suitable for a sealing member. On the other hand, if the content of the artificial graphite is less than 30 parts by mass, the friction coefficient of the crosslinked nitrile rubber member, which is the crosslinked product of the nitrile rubber composition, is not sufficiently low. Also, if the content of the artificial graphite is more than 100 parts by mass, the tensile strength at break and elongation at break of the crosslinked nitrile rubber member, which is the crosslinked product of the nitrile rubber composition, are reduced, and the physical properties become unsuitable for a sealing member. The lower limit of the content of the artificial graphite is preferably 45 parts by mass, and more preferably 60 parts by mass. The upper limit of the content of the artificial graphite is preferably 90 parts by mass, and more preferably 80 parts by mass.
[0023] The nitrile rubber composition may further contain carbon black. In particular, when the nitrile rubber composition is used as a raw material for a hub seal, the hub seal is required to be conductive, so it is preferable that the composition contains carbon black. Examples of the carbon black include SRF, GPF, FEF, HAF, MAF, ISAF, SAF, FT, and MT. These may be used alone or in combination of two or more. As the carbon black, ketjen black or acetylene black, which has excellent electrical conductivity, can also be used.
[0024] When the nitrile rubber composition contains carbon black, the content of the carbon black is preferably 20 to 70 parts by mass based on 100 parts by mass of the nitrile rubber. If the carbon black content is less than 20 parts by mass, the electrical conductivity of the crosslinked nitrile rubber member may not be sufficiently ensured, whereas if the carbon black content exceeds 70 parts by mass, the crosslinked nitrile rubber member may become too hard or the tensile strength at break may become too low.
[0025] The nitrile rubber composition of the present embodiment is vulcanized and molded to form a crosslinked nitrile rubber member, and therefore the nitrile rubber composition may contain a vulcanizing agent (crosslinking agent). The vulcanizing agent may be a conventionally known vulcanizing agent. Specific examples of the vulcanizing agent include sulfur such as powdered sulfur, finely divided sulfur, precipitated sulfur, highly dispersible sulfur, sulfur flowers, sulfur-containing compounds capable of releasing sulfur, and peroxides. Among these, sulfur or sulfur-containing compounds are preferred because they are easy to handle.
[0026] The nitrile rubber composition may further contain a vulcanization aid and / or a vulcanization accelerator in addition to the vulcanizing agent. As the vulcanization aid, a conventionally known vulcanization aid can be used. Specific examples of the vulcanization aid include metal oxides such as zinc oxide, metal carbonates, metal hydroxides, organic acids such as stearic acid and derivatives thereof, amines, etc. These may be used alone or in combination of two or more.
[0027] As the vulcanization accelerator, a conventionally known vulcanization accelerator can be used. The vulcanization accelerator may be appropriately selected according to the type of the vulcanizing agent. Specific examples of the vulcanization accelerator include guanidine compounds, aldehyde-ammonia compounds, thiazole compounds, thiourea compounds, sulfenamide compounds, thiuram compounds, dithiocarbamate compounds, and xanthate compounds. These may be used alone or in combination of two or more.
[0028] The amount of each of the vulcanizing agent, the vulcanization aid, and the vulcanization accelerator may be about 0.1 to 10 parts by mass relative to 100 parts by mass of the nitrile rubber.
[0029] The nitrile rubber composition may contain a plasticizer, such as a phthalate ester, an adipate ester, a trimellitate ester, a polyester, a phosphate ester, a citrate ester, an epoxidized vegetable oil, a sebacic acid ester, an azelaic acid ester, a maleic acid ester, and a benzoic acid ester. Among these, adipates are preferred, and bis[2-(2-butoxyethoxy)ethyl]adipate (DBEEA) is more preferred. The amount of the plasticizer to be mixed may be about 5 to 20 parts by mass based on 100 parts by mass of the nitrile rubber.
[0030] The above-mentioned nitrile rubber composition may further contain additives such as antioxidants, antiaging agents, processing aids such as higher fatty acid esters and metal salts thereof, light stabilizers, lubricants, adhesives, lubricants, flame retardants, antifungal agents, antistatic agents, colorants, and reinforcing agents such as silica, within the range in which the crosslinked product of the nitrile rubber composition (crosslinked nitrile rubber member) does not deteriorate in its normal physical properties.
[0031] The method for preparing the nitrile rubber composition is not particularly limited, and the composition may be prepared by a conventionally known method. For example, the composition may be prepared by uniformly kneading the uncrosslinked nitrile rubber and the artificial graphite, carbon black, a vulcanizing agent, various additives, and the like, which are blended as necessary, using a conventionally known rubber kneading device such as a rubber kneading roll or a Banbury mixer. At this time, the kneading conditions are not particularly limited, but may be, for example, kneaded at a temperature of 30 to 80° C. for 5 to 60 minutes.
[0032] [Cross-linked nitrile rubber material] The crosslinked nitrile rubber member according to the embodiment of the present invention is a crosslinked product of the nitrile rubber composition according to the embodiment of the present invention. The crosslinked nitrile rubber member may be produced using a mold, and the crosslinked nitrile rubber member may be produced by a known rubber molding method such as compression molding, transfer molding, or injection molding. The molding conditions at this time may be appropriately selected depending on the composition of the nitrile rubber composition, and may be, for example, pressure vulcanization at 120 to 200° C. for about 30 seconds to 30 minutes. Furthermore, if necessary, secondary vulcanization may be performed at 120 to 200° C. for about 10 minutes to 10 hours.
[0033] The crosslinked nitrile rubber member is a crosslinked product of the nitrile rubber composition and has a low coefficient of friction, and therefore can be suitably used as a sealing member.
[0034] When the crosslinked nitrile rubber member is used as a sealing member, the preferable normal state physical properties of the crosslinked nitrile rubber member are as follows. The durometer A hardness measured in accordance with JIS K 6253-3:2012 is preferably 70A to 80A. The dynamic friction coefficient measured using a friction and wear tester is preferably 1.2 or less, more preferably 1.0 or less, and further preferably 0.8 or less. The lower limit of the dynamic friction coefficient is usually about 0.1.
[0035] The tensile strength at break (Tb) measured in accordance with JIS K 6251:2017 at a tensile speed of 500 mm / min is preferably 10 MPa or more, and more preferably 12 MPa or more. The elongation at break (Eb) measured in accordance with JIS K 6251:2017 at a tensile speed of 500 mm / min is preferably 300% or more, and more preferably 400% or more.
[0036] The tensile product (MPa·%) is preferably 3000 MPa·% or more, more preferably 4000 MPa·% or more, and even more preferably 5000 MPa·% or more. On the other hand, a preferable upper limit of the tensile product (MPa·%) is 7000 MPa·%. The above tensile product (MPa·%) is the product of the tensile strength at break (Tb) and the elongation at break (Eb), and the value of the above tensile product (MPa·%) is an index of the abrasion resistance of the cross-linked nitrile rubber member.
[0037] When the crosslinked nitrile rubber member is used for a hub seal, it is preferable that the crosslinked nitrile rubber member further has the following normal state physical properties. The volume resistivity (Ω·cm) measured in accordance with JIS K6271-2:2015 (however, at a temperature of 23° C. and a humidity of 65%) is preferably 700 Ω·cm or less, and more preferably 350 Ω·cm or less. Since the hub seal is required to be electrically conductive, a crosslinked nitrile rubber member having a volume resistivity within the above range is preferably used as the elastic member that constitutes the hub seal.
[0038] The crosslinked nitrile rubber member can be used for various applications other than as a sealing member, and can be used in members in which crosslinked nitrile rubber has conventionally been used. The crosslinked nitrile rubber member has a low coefficient of friction and is therefore suitable for use as a member that comes into sliding contact with a counter material.
[0039] [Sealing material] The cross-linked nitrile rubber member is suitable as an elastic member constituting a lip portion that is in sliding contact with a mating member of a seal member. A seal member having a lip portion made of the cross-linked nitrile rubber member is a seal member suitable for reducing torque. The above-mentioned sealing member is suitable as an oil seal, and in particular, when the above-mentioned volume resistivity is low, it is suitable as a hub seal.
[0040] The hub seal is well known as an oil seal used in a hub unit that supports the wheels of an automobile so that they can rotate freely. The hub unit is, for example, composed of a hub shaft, an outer ring, rolling elements, a retainer, and a seal member formed between the hub shaft and the outer ring to seal an annular space in which the retainer and the rolling elements are disposed, and this seal member is the hub seal. The hub seal is, for example, a ring-shaped elastic member having a lip portion that slides against a mating material, which is vulcanized and bonded to a ring-shaped metal core. The hub seal according to the embodiment of the present invention uses the crosslinked nitrile rubber member as the elastic member.
[0041] The above-mentioned hub seal can be manufactured, for example, by placing a metal ring constituting a core bar and the above-mentioned uncrosslinked nitrile rubber composition in a mold, then carrying out a primary vulcanization step in which the nitrile rubber composition is vulcanized under the above-mentioned conditions, and further by demolding the composition from the mold and carrying out a secondary vulcanization as necessary. EXAMPLES
[0042] The present invention will be described in more detail below with reference to examples, but the embodiments of the present invention are not limited to the following examples. In each of the examples and comparative examples, a sheet was prepared to measure normal state physical properties.
[0043] In the examples and comparative examples, the compounding chemicals used in the preparation of the nitrile rubber compositions are as follows. <Nitrile rubber> Krynac 2865 (LANXESS): AN content 28% <Artificial graphite> Artificial graphite A (SEC Carbon): average particle size 6μm Artificial graphite B (SEC Carbon): average particle size 35μm <Carbon black> HAF-HS carbon (Tokai Carbon Co., Ltd., Seast 3H) <Vulcanizing agent> Fine sulfur (Hosoi Chemicals): 325 mesh
[0044] <Other> Stearic acid: TST (Miyoshi Oil Co., Ltd.) Anti-aging agent: TMDQ (Ouchi Shinko Chemical Industry Co., Ltd., Nocrac 224) Plasticizer: DBEEA (Adeka Cizer RS-107, manufactured by Adeka Corporation) Vulcanization aid: Zinc oxide type 2 (manufactured by Sakai Chemical Industry Co., Ltd.) Vulcanization accelerator: TMTD (Ouchi Shinko Chemical Industry Co., Ltd., Noccela TT-P) Vulcanization accelerator: TETD (Ouchi Shinko Chemical Industry Co., Ltd., Noccela TET-G)
[0045] (Examples 1 to 3 and Comparative Examples 1 to 2) (1) The above-mentioned compounding chemicals in the compounding amounts (parts by mass) shown in Table 1 were kneaded with a roll to obtain a nitrile rubber composition.
[0046] (2) After the rubber composition obtained in (1) above was poured into a mold, it was subjected to primary vulcanization at 170°C for 3 minutes to prepare a crosslinked nitrile rubber member (rubber sheet) having a thickness of 2±0.2 mm. Note that secondary vulcanization was not performed.
[0047] [Table 1]
[0048] The following evaluations were carried out using the rubber sheets produced in Examples 1 to 3 and Comparative Examples 1 and 2. The results are shown in Table 2. (1)Hardness: The durometer A hardness was measured using a type A durometer in accordance with JIS K 6253-3:2012. Here, the measurement was performed using three stacked rubber sheets of 2±0.2 mm.
[0049] (2) Tensile strength at break (Tb) and elongation at break (Eb): The sheet was cut to prepare dumbbell-shaped No. 3 test pieces. The prepared test pieces were used to carry out tensile tests in accordance with "JIS K 6251: 2017." The tensile speed was 500 mm / min, and the number of test pieces was three. (3) Tensile product: It was calculated from the tensile strength at break (Tb) and elongation at break (Eb) measured in (2) above.
[0050] (4) Coefficient of kinetic friction: The sheet was cut into a disk shape to prepare a test piece having a diameter of 46 mm and a thickness of 2±0.2 mm. Using this test piece, a friction and wear test was performed under the following test conditions.
[0051] Test conditions Test equipment: Friction and wear tester EFM-III-F (manufactured by Orientec Co., Ltd.) Measuring tool: Outer diameter 25.6 mm, inner diameter 20.0 mm, thickness 15.0 mm, material S45C, surface roughness Ra0.5 μm Vertical load: 5kg Surface pressure: 2.49kg / cm 2 Rotational speed: 500 rpm Circumferential speed: 0.6m / s Test time: 10 minutes Room temperature: 25℃
[0052] (5)Volume resistivity: The measurement was performed according to the method of JIS K 6271-2:2015. The sheet was cut into a test piece of 20 mm width, 80 mm length, and 1.0 mm thickness. The measurement temperature was 23°C and the measurement humidity was 65%.
[0053] [Table 2]
[0054] As shown in Table 2, the crosslinked nitrile rubber member according to the embodiment of the present invention has a low friction coefficient and is suitable as an elastic material that constitutes the lip portion of a low-torque seal member. Furthermore, the crosslinked nitrile rubber members of Examples 1 and 2 contain artificial graphite with a small average particle size, and therefore have excellent electrical conductivity and can be suitably used as an elastic member that constitutes a hub seal. In particular, the crosslinked nitrile rubber member of Example 1 has excellent electrical conductivity and is extremely suitable as an elastic member that constitutes the lip portion of a hub seal.
Claims
1. A crosslinked nitrile rubber member made of a crosslinked product of a nitrile rubber composition containing nitrile rubber and artificial graphite, The average particle size of the artificial graphite is 1 to 10 μm, The content of the artificial graphite is 30 to 100 parts by mass relative to 100 parts by mass of the nitrile rubber, The tensile product, which is the product of the tensile strength at break measured at a tensile speed of 500 mm / min and the elongation at break measured at a tensile speed of 500 mm / min, is 4000 MPa% or more; A cross-linked nitrile rubber material used for sealing materials.
2. The cross-linked nitrile rubber member as described in claim 1, wherein the elongation at break is 300% or more.
3. A crosslinked nitrile rubber member as described in claim 1 or 2, wherein the nitrile rubber has a bound acrylonitrile content of 25 to 30 mass%.
4. A sealing member having a lip portion made of a cross-linked nitrile rubber material described in any one of claims 1 to 3.
5. The sealing member described in claim 4, wherein the cross-linked nitrile rubber member has a volume resistivity of 350 Ω·cm or less measured at a temperature of 23°C and a humidity of 65%, and is an oil seal used in a hub unit.
Citation Information
Patent Citations
Lubricating rubber composition
JP1997324078A
Radio wave absorber
JP2004056064A
Rubber composition and oil seal for reciprocating axle using the same
JP2010065203A
Grease composition for hub unit bearing
JP2014088527A